TINDAKAN PENARIKAN UNIT KENDARAAN YANG DILAKUKAN DEBT COLLECTOR TERHADAP DEBITUR DITINJAU DARI ASPEK HUKUM PIDANA - Jusnizar Sinaga; Muhammad Hamdan; Madiasa Ablisar; Dedi Harianto (USU LAW JOURNAL, 2017)
ABSTRACT In practice the implementation of the debt collector always conduct the act of forcibly and accompanied by violence and inclined to crimes in make withdrawals craft . The formulation of problems related to with the withdrawal of vehicles accompanied by violence that is: How about the collection of arrangement or confiscation of a motor vehicle that carried out by debt collector against a debtor non-performing loans, Do factors for the act of violence carried out by debt collector, How a settlement effort the act of violence carried out by debt collector in terms of the aspect of criminal law. This research is classified as the kind of research juridical normative , study legislation as criminal code and civil law, Regulation president of the Republic Indonesia No. 9 of  2009  about Funding Institution , the act of No. 42 of 1999 about Fiduciary Security, Minister of Finance Regulation No.130/ PMK.010/2012 about Registration Fiduciary for Financing Company, this research also is study case that is focus self intensively on an object particular and learn that as a case. Arrangement about the collection of vehicles stipulated in a financing with fiduciary security contained in the act of fiduciary security number 42 of 1999 And also minister of finance regulation no 130 / PMK. 010 / 2012 . Factors for the occurrence of violence carried out by debt collector consists of institutions too pursue the target of , lack of awareness of debtors , lack of knowledge of the laws the third party or debt collector and debtors , then influenced by a characteristic debt collector. On a settlement case the act of violence carried out by debt collector by virtue of position cases decisions of the supreme court number .242 / pid.b / 2013 / pn.jmb where debt collector proven to commit crimes dispossession by violence in when make withdrawals vehicles with a profitable purpose self or another person and to eliminate receivable debtors with against the right . Keywords: Debt collector, Crimes Dispossession by Violence, Consumen Financing